Konservatisme Akuntansi dan Kinerja Perusahaan di Indonesia - Suwarno Suwarno; Suwandi Suwandi; Mu'minatus Sholichah (Akuntabilitas, 2022)
This study aims to confirm the relationship between accounting conservatism and the financial performance of companies in Indonesia in the 2019 period. Accounting conservatism is still debated between standard setters and accountants. The accountants argue that accounting conservatism is still needed to reduce the opportunistic behavior of managers. Meanwhile, accounting standard setters stated that accounting conservatism had an impact on biased financial statements. The research sample was selected with several criteria so that 564 companies were obtained. Panel data were analyzed by regression and the results showed that conservative accounting had an effect on Return On Assets (ROA). Accounting conservatism will reduce information asymmetry, which will reduce managers’ opportunistic behavior and increase investment efficiency and improve company performance. However, accounting conservatism has no effect on firm value (Tobin’s Q). Accounting conservatism will cause financial statements to tend to be biased because financial statements cannot describe the actual situation. Therefore, financial statements are not able to predict future cash flows.